2019
DOI: 10.1371/journal.pone.0218775
|View full text |Cite
|
Sign up to set email alerts
|

Birds vs bricks: Patterns of species diversity in response to urbanization in a Neotropical Andean city

Abstract: Urbanization is currently one the most important causes of biodiversity loss. The Colombian Andes is a well-known hotspot for biodiversity, however, it also exhibit high levels of urbanization, making it a useful site to document how species assemblages respond to habitat transformation. To do this, we compared the structure and composition of bird assemblages between rural and urban habitats in Armenia, a medium sized city located in the Central Andes of Colombia. In addition, we examined the influence of urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 86 publications
(117 reference statements)
2
14
0
6
Order By: Relevance
“…Previous studies in Europe have shown that common species, such as house sparrows (Passer domesticus) and common starlings (Sturnus vulgaris), preferentially settle in urban sites with parks and gardens (Chamberlain et al 2007;Morelli et al 2018;Murgui 2009). Urban birds can find most of their food resources, which consist mostly of seeds and insects, in understory vegetation areas (Carvajal-Castro et al 2019;Huang et al 2015;Müller et al 2018). Moreover, understory vegetation areas can provide material for nest building, such as grass, straw, and twigs (Anderson 2006;Mainwaring and Healy 2019).…”
Section: Benefits Of Vegetation For Avian Biodiversitymentioning
confidence: 99%
“…Previous studies in Europe have shown that common species, such as house sparrows (Passer domesticus) and common starlings (Sturnus vulgaris), preferentially settle in urban sites with parks and gardens (Chamberlain et al 2007;Morelli et al 2018;Murgui 2009). Urban birds can find most of their food resources, which consist mostly of seeds and insects, in understory vegetation areas (Carvajal-Castro et al 2019;Huang et al 2015;Müller et al 2018). Moreover, understory vegetation areas can provide material for nest building, such as grass, straw, and twigs (Anderson 2006;Mainwaring and Healy 2019).…”
Section: Benefits Of Vegetation For Avian Biodiversitymentioning
confidence: 99%
“…Green spaces are a key element for biodiversity conservation in cities since they represent available habitat for a wide range of organisms (Cornelis and Hermy, 2004;MacGregor-Fors et al, 2016) and much of the research on diversity in urban green spaces has focused on birds (Magle et al, 2012;Beninde et al, 2015). Studies have mainly reported reductions in both the number of species and diversity indices together with compositional changes (Carvajal-Castro et al, 2019;Di Pietro et al, 2020 but see Benitez et al, 2021). Although species richness has been a widely-used measure of biodiversity to assess the effect of urbanization on bird communities (Rush et al, 2014;Canedoli et al, 2017;Matthies et al, 2017) the assumption of species being equivalent may not be ecologically precise (Chave, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the wide diversity of environments and behaviors and, consequently, greater exposure to negative effects associated with habitat transformation, such as mortality from window collisions, exposure to new diseases and predators, birds have been used to study the effects of urbanization on the diversity of species (Carvajal-Castro et al, 2019).…”
Section: Discussionmentioning
confidence: 99%